Metaverse: A Promising Future for the Tourism Industry and MSMEs Post-Covid-19 Pandemic - Gegung, Eunike Martha (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
This study begins by explaining the tourism industry during and after COVID-19 and explaining the metaverse concept, including how it transforms the tourism industry and MSMEs. This study proposes a literature method to provide a rationale for the issue. The data was collected mainly through written evidence such as documents, journal articles, scholarly books, research reports, and online websites. Then the content analysis was used for analysing the data. Despite research’s expansion on metaverse attributes, the notion of metaverse related to the tourism industry and MSMEs need to be observed more. This study notes that the use of metaverse in the tourism industry and MSMEs has many benefits. It revolutionises the tourism industry and offers new sales channel for small business owners.